Mavacamten for Obstructive Hypertrophic Cardiomyopathy: Rationale for Clinically Guided Dose Titration to Optimize Individual Response - Anjali T. Owens; Milind Desai; Matthew T. Wheeler; Anna Rodonski; Samira Merali; Amy J. Sehnert; Sara Saberi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Mavacamten is the first and only cardiac myosin inhibitor approved in 5 continents for the treatment of adults with symptomatic New York Heart Association class II and III obstructive hypertrophic cardiomyopathy. An evidence‐based rationale was used to develop individualized mavacamten dosing, guided by commonly used clinical parameters. Echocardiography is recommended as part of routine clinical assessment of patients with hypertrophic cardiomyopathy, and left ventricular (LV) outflow tract gradient and LV ejection fraction are parameters that can be readily assessed and monitored by echocardiography. Therefore, an echocardiography‐based, clinically guided dose‐titration strategy was developed to optimize patient benefit from mavacamten for the treatment of symptomatic obstructive hypertrophic cardiomyopathy while minimizing the risk of LV ejection fraction reduction. Results from clinical trials paired with extensive modeling and simulation analyses support a dose‐titration and monitoring strategy based on serial echocardiographic measures of Valsalva LV outflow tract gradient and LV ejection fraction. This dosing approach allows for the identification of the lowest individualized mavacamten dose and exposure required to provide improvements in LV outflow tract obstruction, functional capacity, and symptoms. Mavacamten is primarily metabolized by CYP2C19 (cytochrome P450 2C19), and CYP2C19 metabolizer phenotype has an effect on mavacamten exposure. Therefore, this approach has also been demonstrated to provide a favorable safety profile irrespective of patients' CYP2C19 metabolizer status. The dose‐titration strategy includes additional considerations for the potential onset of systolic dysfunction in the context of intercurrent illness, and for the potential of drug–drug interactions with inhibitors and substrates of cytochrome P450 enzymes. This posology is reflected in the mavacamten US prescribing information.